Obtenção de filmes de pectina contendo quercetina para uso no tratamento de feridas cutâneas - Colombari Neto, Jean (2021)
The aim of this study was to obtain pectin films, extracted from industrial orange wastes, containing quercetin, and to evaluate its use as a wound healing film. The extraction was executed in an aqueous medium at pH 2.5, under heating and stirring, and precipitated and purified in an alcoholic medium. Looking to optimize the processes, in obtaining the films, an experimental 23 factorial design complete was used, with duplicate of the central point, in which the studied variables were: polymer concentration (pectin), concentration of the bioactive molecule (quercetin) and, concentration of the plasticizer (glycerol). The yield for the extraction process was 15%. The determination of pectin carboxyl groups showed values of 7.36% ± 0.027 for free carboxyl groups and 8.67% ± 0.062 for esterified carboxyl groups. The degree of esterification was on average 54.07% ± 0.088, classifying the material as a pectin with a high degree of methoxylation. The viscosimetric data described a Huggins intrinsic viscosity of 76.64 mL.g-1. The measured viscosimetric molar mass was ≈ 333,000 g.mol-1. In the production of films, the addition of plasticizer favored obtaining a more flexible and resistant material. The morphological analysis allowed evaluating the uniformity of the films, and possible discontinuities. Thickness values ranged from 0.363 ± 0.004 mm to 0.170 ± 0.015 mm for the F9 and F7 films, respectively. The opacity ranged from 6.856 ± 0.274 Abs.mm to 1.833 ± 0.096 Abs.mm F8 and F5 respectively. For the solubility data, the values ranged from 88.204 ± 0.314 to 94.711 ± 0.565 for the F9 and F3 films, respectively. TVA values range from 883.460 g/d.m2 to 1208.22 g/d.m2 for F1 and F7 films, respectively. For the mechanical analysis, the values found for the Young's modulus were from 0.0605 MPa to 0.0017 MPa for the F9 and F3 films, respectively. The yield strength values ranged from 0.0847 MPa to 0.9783 MPa for the F8 and F7 films, respectively. The tensile strength of the films ranged from 0.6899 MPa to 4.7024 MPa, for the F3 and F6 films, respectively. The changes observed in the diffractograms describe a change in the crystallographic behavior of the precursors and films obtained, as well as the thermal behavior observed in the differential scanning calorimetry and TGA analysis. Infrared spectroscopy analysis demonstrated the characteristic bands of pectin precursors at 3421 cm-1, 1621 cm-1, 1749 cm-1 and 1019 cm-1; and quercetin, characteristic of phenolic groups 1615 cm-1, 710 cm-1 and 770 cm-1; the spectra of the films showed bands. The antioxidant capacity of the films presented values ranging from 40.32 ± 0.67% to 45.37 ± 0.17% for the F3 and F5 films, respectively. The antimicrobial activity test did not show the formation of inhibition halos, however, there was no evidence of the growth of microorganisms on or under the films. Thus, corroborating the data found in this research, it was found that the F7 film has great potential for use as dressings for wounds, taking due care in its applications.